Development of 13 Mozambican Municipalities in Central and Northern Mozambique : Summary report - World Bank (World Bank, 2012)
The objective of this study on the Development of 13 Mozambican Municipalities in Central and Northern Mozambique is to assess the impact that the 2008 reforms on own-source revenues is having on the municipal revenue potential. To do so, it calculates the revenue potential of four fiscal and three non-fiscal revenue sources. The analysis shows that there is substantial untapped revenue potential at the municipal level, with estimates indicating that -in the case of the most buoyant local revenue sources- municipalities are only collecting about half of the revenue potential. In the worst cases, municipalities are collecting far less than 10 percent of the total revenue potential of a local revenue source. The fact that a revenue gaps exists is not only an indication of weak municipal performance. Municipalities have relatively recently been created and it takes time, capacity, and effort, to consolidate their revenue functions. Tax administration is overall still weak and a series of vacuums exist on the municipal fiscal legislation. The analysis reveals that the current revenue instruments at the disposal of municipalities are generally appropriate municipal revenue instruments, so that efforts at the national and municipal levels should be made to build the capacity of the local tax administration to collect these revenues. The report provides specific suggestions on ways to strengthen the revenue collection for the main municipal revenue instruments. However, in addition to increasing municipal tax effort, the expenditure needs of municipalities are so demanding that additional intergovernmental transfers and tax sharing arrangements should also be considered as a building block of municipal finances in Mozambique. The results of this study aim to become part of the ongoing dialogue with the municipalities and national tax authorities to expand the understanding of municipal revenues in Mozambique on the basis of more sound empirical evidence. The scope of this analysis was limited to a sample of six municipalities. In-depth case studies were prepared for each of these municipalities, upon which the current Summary Report is based. The six case municipalities include: Beira, Cuamba, Marromeu, Nacala, Ribaue, and Vilankulo. To bring the Summary Report and the six municipal cases together in the most effective way, the current report follows the same structure as each of the municipal cases. The diagnosis of the current situation is presented in Section 2, followed by a discussion on the estimation of municipal revenue potential in Section 3. Proposals and recommendations regarding the strengthening of municipal revenue collection are presented in Section 4.